Innovation of UNESCO-MAB: An Opportunity for the Territorial and Sustainable Development of the Arganeraie Biosphere Reserve - Wafaa Benhsain; Said Boujrouf (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: Morocco has implemented several strategies and rules for saving biodiversity and safeguarding natural and territorial riches in protected regions since the release of the Vizier Decree on January 19, 1942. Within this context, the UNESCO MAB designation encourages creativity in the World Network of Biosphere Reserves. However, its goal of reconciling protection and resource management in order to generate territorial and sustainable development possibilities has been criticised. This article aims to focus on the deficiencies of local population involvement in the Arganeraie Biosphere Reserve in preserving the forest environment, as well as the role of innovations brought about by the UNESCO MAB label commitment in this reserve rich in remarkable biodiversity and threatened endemic resources. Methodology: The study used critical and territorial approaches, implementing a documentary analysis of MAB programs and strategies and selecting innovations from the latter. Then confronted these innovations with the reality observed in the ABR field through a qualitative human and social sciences analysis. This research was founded on the results of fieldwork conducted as part of the Erasmus + EduBioMed Project. This work was carried out through a documented study of MAB programs and strategies, as well as the clash of advances introduced by the latter with the actuality of the field of ABR. Findings: According to this study, the majority of social, economic, and territorial innovations coming from the use of the UNESCO MAB label have led to significant changes in local communities. However, the impacts are more concentrated in regions where the actors have a stronger presence. Implications/Novel Contribution: The qualitative results of the study are crucial for understanding the reality of RBA which is a specific territory concerning the various forms of innovation brought about by the UNESCO MAB label. The research brings several policy and implementation insights for future programs implemented by UNESCO in Morrocco and overall, across the globe. .